ChemInform Abstract: Alkaloid Inspired Spirocyclic Oxindoles from 1, 3‐Dipolar Cycloaddition of Pyridinium Ylides. Issue 4 (28th January 2014) - Day, Jonathan; Uroos, Maliha; Castledine, Richard A.; Lewis, William; McKeever‐Abbas, Ben; Dowden, James
Abstract Cycloaddition reactions between pyridinium ylides and 3‐alkenyl oxindoles (I) proceed in high yields and with good regio‐ and diastereoselectivity.